Transparent high-performance SiOxNy/SiOx barrier films for organic photovoltaic cells with high durability. (March 2017) - Won Lim, Ju; Kyu Jin, Chang; Yong Lim, Keun; Jae Lee, Yun; Kim, Sung-Ryong; Choi, Byung-Il; Whan Kim, Tae; Ha Kim, Dong; Kyung Hwang, Do; Kook Choi, Won
Abstract: The science and technology of organic electronics have made consistent progress. However, the long-term stability of organic devices is a critical issue that remains to be resolved. Encapsulation is a straightforward and practical means to protect organic materials from oxygen or moisture and thus improve air stability. Here, we report a high-performance flexible inorganic SiNx /SiOx Ny hybrid barrier film for application in organic solar cells (OSCs). This hybrid barrier film shows average transmittance of 85.5% and a water-vapor transmission rate of 7.1×10 –5  g m −2 day −1 . In OSCs comprising poly[4, 8-bis[(2-ethylhexyl)oxy]benzo[1, 2-b:4, 5-bA]dithiophene-2, 6-diyl][3-fluoro-2-[(2-ethylhexyl)carbonyl] thieno[3, 4-b]-thiophenediyl] (PTB7) and [6, 6]-phenyl-C70 -butyric acid methyl ester (PC70 BM), which were encapsulated by the SiNx /SiOx Ny hybrid barrier film, the power-conversion efficiency remained above 86% of the initial value even after 2000 h of storage in air, which is comparable to that obtained for a device encapsulated by a glass lid. Graphical abstract: The high performance flexible inorganic SiNx /SiOx Ny hybrid barrier film is proposed for application in organic solar cells (OSCs), which shows average transmittance of 85.5% and WVTR value of 7.1×10 −5  g m −2 day −1 . In PTB7:PC70 BM OSCs encapsulated by the SiNx /SiOx Ny hybrid barrier film, PCE reamins above 86% of the initial value even after 2000 h storage in ambient air, comparable to that obtained for a device encapsulated by a glass lid. Highlights: A inorganic SiNx /SiOx Ny hybrid barrier film prepared on a flexible substrate. The SiNx /SiOx Ny hybrid barrier film shows WVTR of 7.1×10 -5 g m -2 day -1 . The PCE of encapsulated OSCs remained 86% of initial efficiency even after 2000 h.